Performance and consensus - Bourgeois, L. J. (Strategic Management Journal, 1980)
Abstract Top management consensus on corporate objectives and on the competitive weapons employed to attain them was studied in 12 non‐diversified public corporations. It was found that while agreement on both is associated positively with economic performance, agreement on means is significantly more important—in fact, agreement on goals without agreement on means correlates with poor performance. This suggests that strategy makers should concentrate on reaching consensus concerning means rather than ends (corporate goals) when formulating strategies for single‐mission enterprises.